Analysis of land resources balance in Nusa Tenggara Timur Province - Putri R.F.; Rokhim A.A.; Prakosa M.G.; Hastari N.R.F.; Adhesti Y.M.P.; Junaedi R.N.; Ramdani H.P.; Omar R.C. (IOP Publishing Ltd, 2023)
Agricultural robots; Land use; Natural resources; Agricultural land; Human activities; Land resources; Land utilization; Non-agricultural lands; Plantation land; Population pressure; Resource balances; Agriculture